MOTOR ABILITIES IN BOYS ELEmeNTARY SCHOOL - Ivan Janković; Slobodan Stojiljković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
The pri mary goal of the re se arch is to de ter mi ne the dif fe ren ces in mo bi lity ca pabi lityes of boys at early school age, bet we en the ones in vol ved in the tra i ning pro cess at sports clubs and the ones who ha ve no ot her sports ac ti vi ti es be si des the re gu lar clas ses of physi cal edu ca tion at school. The te sted par ti ci pants we re 63 boys at the age of 9 ± 6 months. The gro up of boys who we re in vol ved in the tra i ning pro ces, con si sted of 36 boys and gro up of boys not in vol ved in sports clubs con si sled of 27 boys. The as ses sment of the ir mobylity ca pa bi li ti es was con duc ted using 12 va ri a bles. The ca no ni cal di scri mi na ti ve analysis sho wed that the re are glo bal dif fe ren ces bet we en the two sam ples in fa vo ur of boys in vol ved in sports clubs which is ex pla i ned by the tran sfor ma ti o nal pro ce es of tra i ning and di rec ted se lec tion.